(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article discusses the significance of digital technologies in education and how they should be integrated into the learning process. While technologies can serve as valuable tools in education, their effective application in working with preschool and pre-primary children poses challenges due to children's developmental characteristics, specific needs, and educators' competencies in integrating information technologies (IT) into the learning process. The study aims to assess the expression of IT competence among preschool and pre-primary educators. The research methods include scientific literature and document analysis, a written survey (questionnaire), and both quantitative and qualitative data analysis. The analysis of scientific literature and documents highlights that preschool and pre-primary educators' IT competence encompasses key abilities such as digital content creation, digital communication, safety, and problem-solving. Essential skills include using IT applications and digital tools (computers, tablets, interactive whiteboards) to enhance children's artistic expression and writing skills, as well as understanding and effectively communicating digital terminology to children. The study also identifies opportunities for integrating IT into the learning process, such as educational games, video content viewing, online collaboration, information retrieval, content creation, and voice recording exploration. Empirical findings reveal that most respondents can define IT competence and recognize its increasing importance. Interactive floors and interactive whiteboards are the most commonly used digital tools in early childhood education. However, educators often face challenges such as a lack of IT resources, slow internet connectivity, limited time for IT use, and insufficient knowledge or time for professional development. IT is frequently used for exploring e-books, fairy tales, maps, educational videos, and online information searches. However, tools such as voice recorders, printers, and cameras are rarely utilized, and activities such as creating presentations, illustrations, remote communication, and playing educational games remain infrequent.